Changing interpretation of chromosomal microarray over time in a community cohort with intellectual disability. Issue 2 (5th December 2013) - Palmer, Emma; Speirs, Helen; Taylor, Peter J; Mullan, Glenda; Turner, Gill; Einfeld, Stewart; Tonge, Bruce; Mowat, David
Abstract Chromosomal microarray (CMA) is the first‐line diagnostic test for individuals with intellectual disability, autism, or multiple congenital anomalies, with a 10–20% diagnostic yield. An ongoing challenge for the clinician and laboratory scientist is the interpretation of variants of uncertain significance (VOUS)—usually rare, unreported genetic variants. Laboratories differ in their threshold for reporting VOUS, and clinical practice varies in how this information is conveyed to the family and what follow‐up is arranged. Workflows, websites, and databases are constantly being updated to aid the interpretation of VOUS. There is a growing literature reporting new microdeletion and duplication syndromes, susceptibility, and modifier copy number variants (CNVs). Diagnostic methods are also evolving with new array platforms and genome builds. In 2010, high‐resolution arrays (Affymetrix 2.7 M Oligo and SNP, 50 kB resolution) were performed on a community cohort of 67 individuals with intellectual disability of unknown aetiology. Three hundred and one CNVs were detected and analyzed using contemporary resources and a simple scoring system. Thirteen (19%) of the arrays were assessed as potentially pathogenic, 4 (6%) as benign and 50 (75%) of uncertain clinical significance. The CNV data were re‐analyzed in 2012 using the contemporary interpretative resources. There was a statistically significant difference in the assessment of individual CNVs (P < 0.0001). An additional eight patients were reassessed as having a potentially pathogenic array (n = 21, 31%) and several additional susceptibility or modifier CNVs were identified. This study highlights the complexity involved in the interpretation of CMA and uniquely demonstrates how, even on the same array platform, it can be subject to change over time. © 2013 Wiley Periodicals, Inc.